Modal Auxiliaries as Epistemic Devices in Marking Scientific Researchers’ Uncertainty on Covid-19 - Nur Azwin Zulkarnain; Ridwan Wahid; Jariah Mohd Jan (JALL (Journal of Applied Linguistics and Literacy), 2023)
The early phase of the COVID-19 pandemic caused a lot of pressure to scientists due to the novel nature of the coronavirus. As experts in the field, they were expected to produce only reliable information. Owing to the limited data available at the time, there were many uncertainties surrounding the virus. However, studies that looked into how the uncertainties were navigated are scarce. This corpus-based study investigates this issue using the system value of modal operators by Halliday and Matthiessen (2014), along with Dong et al.’s (2020) classification of COVID-19 research themes to explore levels of scientific researchers’ certainty in presenting information about coronavirus. Specifically, their choices of modal auxiliaries as epistemic devices are analysed. Results demonstrate that researchers mainly conduct studies on epidemiology with the lowest degree of certainty by utilising modals such as may, could and might. Furthermore, while some of the propositions expressed do display researchers’ assumptions of possibilities, they however, are presented with insufficient evidence. These findings help to untangle scientific researchers’ expressions of uncertainty and certainty through their use of epistemic devices and contribute to a better understanding of their intentions in conveying vital information.